Bahasa Inggris: Bahasa Inggris - Agung Bayu Saputro; Venia Setyarandini (Department of Architecture, Faculty of Engineering and Computer Science, Universitas Muhammadiyah Semarang, 2026)
Thermal comfort is a critical factor in the environmental performance of rural residential buildings, particularly in hot-humid regions where passive strategies largely depend on material characteristics. In Cuntel Village, Semarang Regency, Indonesia, most houses are constructed using locally sourced materials, including clay roof tiles, metal sheets, red brick, lightweight concrete blocks, timber panels, earthen floors, cement plaster, and ceramic tiles. This research investigates how the use of these materials affects indoor thermal comfort performance. A mixed-method approach was employed, combining in-situ measurements of indoor air temperature and relative humidity with an occupant thermal perception survey. The measured data were assessed based on ASHRAE Standard 55 and SNI 6390:2011. The findings indicate significant differences in heat retention and dissipation among material configurations, with clay tile roofing and ceramic flooring contributing to lower indoor temperature fluctuations compared to metal roofing and earthen floors. Survey responses suggest that thermal acceptability aligns with material combinations that support passive heat regulation. These results emphasize that informed material selection plays a substantial role in shaping thermal comfort outcomes in rural housing. The study provides a basis for promoting climate-responsive material utilization to improve residential thermal performance in Indonesia’s rural contexts.